GASTRITIS AND HELICOBACTER PYLORI IN CHILDREN - PRIMARY AND SECONDARY ENDOSCOPIC DIAGNOSIS - V.V. Lupu; Gabriela Paduraru; Ancuta Ignat; Eliza Tighici-Saizu; Claudia Olaru; Nicoleta Gimiga; Angelica Cristina Marin; Cornelia Savescu; Ioana Florea; Marin Burlea (Amaltea Medical Publishing House, 2015)
The infection with Helicobacter pylori (H pylori) represents an important issue of public health. Aim. Establishing the prevalence of H. pylori infection in children and presenting the cases according to the gastritis type by performing upper digestive endoscopies. Material and method. The retrospective study referred to a period of 5 years and included 1269 children evaluated by upper endoscopy to establish the H. pylori infection rate. Results. The frequency of H. pylori in the case of acute gastritis was signifi cantly more reduced (34.78%) than in the case of chronic gastritis (54.94%). Referring to the 10 types of gastritis, the most frequent ones are purpuric (43.66%), nodular purpuric (25.93%) and nodular antral (15.84%). At the other end, atrophic and hypertrophic gastritis were positioned. The most frequent associations pointed out endoscopically are those with 1st degree esophagitis - 51.6%, duodenitis - 45.07% and purpuric duodenitis - 24.74%. Conclusions. The H. pylori infection is the most frequent etiologic factor for chronic gastritis (54.94%). The early identifi cation of the infection is essential to destroy the bacteria and to prevent the development of various types of gastritis that are later on endoscopically identifi ed.